Petshop Business Performance Analysis: An Marketing Approach - Rusdiaman Rauf; Hardianti Hardianti; Muhammad Yunus (Jurnal Economic Resource, 2023)
The need for a Petshop business in Makassar City is needed along with the increasing love of people for pets so that a marketing strategy is needed in marketing services for the products they sell. The population of this study was service users (3) three petshops in Makassar City, while the determination of this sample used the Probability Sampling Technique which amounted to 69 people in a random way without paying attention to the level that existed in the population members. Data collection techniques used are observation, questionnaires and direct interviews to parties related to the problem under study. The data were analyzed using multiple lenear regression analysis techniques, t-test, f-test and coefficient of determination with the help of SPSS 23 program.The results showed that (i) direct marketing communication did not have an effect on customer satisfaction, (ii) service quality directly affected and significantly affected customer satisfaction, (iii) simultaneously communication and service quality had a positive effect on customer satisfaction. Based on the coefficient of determination obtained from the results of data analysis, it is known that marketing communication and service quality have an influence of 61.6% on customer satisfaction of Petshop business in Makassar.